2007
DOI: 10.1111/j.1365-313x.2006.03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of ferredoxin‐NADP+‐oxidoreductase using knock‐out mutants of Arabidopsis

Abstract: SummaryIn Arabidopsis thaliana, the chloroplast-targeted enzyme ferredoxin-NADP + -oxidoreductase (FNR) exists as two isoforms, AtLFNR1 and AtLFNR2, encoded by the genes At5g66190 and At1g20020, respectively. Both isoforms are evenly distributed between the thylakoids and soluble stroma, and they are separated by twodimensional electrophoresis in four distinct spots, suggesting post-translational modification of both isoforms. To reveal the functional specificity of AtLFNR1, we have characterized the T-DNA ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
107
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 56 publications
16
107
0
1
Order By: Relevance
“…FNR is a ubiquitous flavoenzyme that oxidizes the final reduced product of the photosynthetic electron transport chain, ferredoxin (Fd), to reduce NADP + , resulting in ATP production. Therefore, FNR levels (activity) regulate cellular NADPH/NADP + and ATP/AMP ratios (16,22). Consistent with LN induction of FNR1 expression, we detected higher NADPH/NADP + and lower AMP/ATP ratios in WT plants in LN conditions than in NN conditions (P < 0.05).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…FNR is a ubiquitous flavoenzyme that oxidizes the final reduced product of the photosynthetic electron transport chain, ferredoxin (Fd), to reduce NADP + , resulting in ATP production. Therefore, FNR levels (activity) regulate cellular NADPH/NADP + and ATP/AMP ratios (16,22). Consistent with LN induction of FNR1 expression, we detected higher NADPH/NADP + and lower AMP/ATP ratios in WT plants in LN conditions than in NN conditions (P < 0.05).…”
Section: Resultssupporting
confidence: 70%
“…These results suggest that CRY1 may work downstream of FNR1 in the N-signaling pathway. Although previous studies reported that both the fnr2 mutant (16,22) and the cry2 mutant (19, 23) had a late-flowering phenotype, here these mutants exhibited normal responses to N changes (P < 0.05; SI Appendix, Table S3), suggesting that neither FNR2 nor CRY2 plays an essential role in N-regulated flowering time.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Based on KEGG analysis of the four G. max-specific genes, Glyma01g37051 is involved in energy metabolism (ko00190 and ko00194), Glyma13g36351 and Glyma15g39541 in lipid metabolism (ko00590, ko00591 and ko00592), and Glyma15g39596 in cell growth and death (ko04210). Glyma01g37051 is a homolog of AtLFNR1 (ferredoxin-NADP + -oxidoreductase, AT5G66190), which in Arabidopsis is involved in photosystem Idependent cyclic electron now and affects rosette size 15 .…”
Section: Variation Between G Soja and Gmaxw82mentioning
confidence: 99%
“…Thus, C and N may regulate flowering through different pathways. Given that nitrogen levels regulate ferredoxin-NADP C -oxidoreductase and ATP synthesis rate (energy metabolism flow), 3,11 nitrogen metabolism and carbon metabolism may be tightly linked with each other. The crosstalk between C metabolite signals and N metabolite signals needs further investigations.…”
Section: Introductionmentioning
confidence: 99%